Can Answers to the Health Workforce Crisis Be Found in Equity-Informed Digital Health? - Helen Novak Lauscher, Chad Kim Sing, Chantz Strong, Anita Palepu, Jason Jaswal, Dietrich Fürstenburg, Nelly D. Oelke, Patricia Kay Pearce and Kendall Ho (HealthcarePapers, 2024)
In this paper, we describe current pressures on health human resources (HHRs) in the Canadian context and related factors that impact equity-deserving communities/populations. We explore issues of HHR challenges in rural, remote and urban underserved contexts and explore the associated benefits and challenges of incorporating digital health (DH). We present examples and evidence of integrating hybrid models of care as a means of supporting HHRs via DH in the publicly funded health system.
Keywords: health human resources, digital health, rural, remote, urban underserved, hybrid models of care, health equity